The 16189 variant of mitochondrial DNA occurs more frequently in C282Y homozygotes with haemochromatosis than those without iron loading. Issue 1 (16th January 2004) - Livesey, K J; Wimhurst, V L C; Carter, K; Worwood, M; Cadet, E; Rochette, J; Roberts, A G; Pointon, J J; Merryweather-Clarke, A T; Bassett, M L; Jouanolle, A-M; Mosser, A; et al.
Abstract : Background: Patients with hereditary haemochromatosis (HH) are usually homozygous for the C282Y mutation in the HFE gene. They have variable expression of iron overload and present with a variety of complications, including liver disease, diabetes, arthropathy, fatigue, and cardiomyopathy. The mitochondrial 16189 variant is associated with diabetes, dilated cardiomyopathy, and low body fat at birth, and might contribute to genetic predisposition in further multifactorial disorders. The objective of this study was to determine the frequency of the 16189 variant in a range of patients with haemochromatosis, who had mutations in the HFE gene. Methods: Blood DNA was analysed for the presence of the 16189 variant in British, French, and Australian C282Y homozygotes and controls, with known iron status, and in birth cohorts. Results: The frequency of the mitochondrial 16189 variant was found to be elevated in individuals with haemochromatosis who were homozygous for the C282Y allele, compared with population controls and with C282Y homozygotes who were asymptomatic (42/292 (14.4%); 102/1186 (8.6%) (p  =  0.003); and 2/64 (3.1%) (p  =  0.023), respectively). Conclusions: Iron loading in C282Y homozygotes with HH was exacerbated by the presence of the mitochondrial 16189 variant.